2017
DOI: 10.1002/elps.201700013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactant species and electrophoretic medium composition on the electrophoretic behavior of neutral and water‐insoluble linear synthetic polymers in nonaqueous capillary zone electrophoresis

Abstract: We have recently demonstrated the separation of neutral and water-insoluble linear synthetic polymers in nonaqueous capillary zone electrophoresis (NACZE) using a cationic surfactant of cetyltrimethylammonium chloride (CTAC). In this study, eight ionic surfactants were investigated for the separation of four synthetic polymers (polystyrene, polymethylmethacrylates, polybutadiene, and polycarbonate); only three surfactants (CTAC, dimethyldioctadecylammonium bromide, and sodium dodecylsulfate) caused their separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The apparatus and procedure are similar to those described in our previous study [18]. A commercial CAPI-3100 instrument (Otsuka electronics, Osaka, Japan) with a fused-silica capillary of i.d.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The apparatus and procedure are similar to those described in our previous study [18]. A commercial CAPI-3100 instrument (Otsuka electronics, Osaka, Japan) with a fused-silica capillary of i.d.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous research, we demonstrated the separation of neutral linear synthetic polymers by NACZE using three-solvent mixtures containing an ionic surfactant (CTAC, dimethyldioctadecylammonium bromide (DMDOAB), or sodium dodecylsulfate (SDS)) [17,18]. As reported in our previous paper, the solubility of CTAC, DMDOAB, and SDS in THF is lower than 1 mM [18]. In this study, the solubility of P 66614 Cl was measured to be over 500 mM in THF as well as MeOH and ACN at room temperature.…”
Section: Effect Of Ionic Liquid Concentrationmentioning
confidence: 99%
See 3 more Smart Citations